Innovation in gallery education: Art experimental workshops in the Moravian Gallery - Burešová, Lenka (Tudásmenedzsment, 2023)
The framework of this paper describes my own experience as an independent gallery educator in a museum institution, implementing a "classic educational format" focusing on experiential teaching activities for schools, practical teaching activities for the public in order to develop a "new educational format" for teaching within a gallery space. These formats of a gallery educational activities were tested in the Moravian Gallery in Brno, Czech Republic and a series of free-time artistic and experimental workshops called ARTS'UP_ ART ON EX were created and open to the public. The gallery term for these activities was coined as "edutainment". The result was documented and curated in a permanent exhibition titled Art is Here -"New art". Part of this research is an examination of galleries educational activities that explores the theory and the practical ideas to define the formats of education within gallery spaces to develop a programme of activities aimed to children and the public. The aim is to explore other formats for spaces to learn by bringing the "educational institution" and "cultural institutions", together by developing a common ground to create a curriculum for visiting schools to create a new platform for teachers to expand the model of education. The practical result of the research is the presentation of a gallery project created for the permanent exhibition of modern art in the Moravian Gallery. Since no educational material detailing the social science concept of modernism was created for the exhibition itself, the creation of a methodological sheet that contains structured educational content with a proposal for activities that allows elements of art pedagogy and cross-curricular links. In addition, the result enriches a constructivist-oriented model of teaching that can be used in galleries or can serve as a strategy point to develop new educational spaces.